The Binding of Isaac and Child Sacrifice in the Ancient Near East: A Comparative Analysis - Lumingkewas, Marthin Steven (Indonesian Journal of Religious, 2025)
Sacrifice in general in the sense of some people is giving something as a form of loyalty or self-devotion in various forms, such as property, even life will be given. If we look at and have heard history, several civilizations in the past had immoral and inhumane religious practices. The practice of child sacrifice has been a subject of considerable interest and debate within biblical and ancient history studies. This study examines the narrative of the Binding of Isaac (Genesis 22) within the broader religious and cultural context of child sacrifice in the Ancient Near East (ANE). While the Akedah shares thematic similarities with ANE sacrificial traditions—particularly the motif of offering a firstborn to a deity—it simultaneously presents a profound theological and ethical departure from those practices. Drawing on textual, archaeological, and comparative literary evidence from Mesopotamian, Canaanite, and Phoenician sources, this paper explores the ideological function of child sacrifice in ANE societies as an expression of extreme piety, covenantal obligation, and ritual appeasement. In contrast, the Genesis account frames the near sacrifice not as an act of ritual devotion, but as a divine test of Abraham’s faith and trust. Significantly, the intervention of YHWH at the climax of the story—commanding Abraham not to harm Isaac and providing a ram as a substitute—functions as a narrative critique of human sacrifice and a theological reorientation. Rather than affirming the cultural norm of child sacrifice, the Akedah undermines its legitimacy and introduces a new paradigm: one that emphasizes divine provision, the sanctity of life, and ethical boundaries in worship. This paper argues that the story’s literary form and theological message must be understood both in dialogue with and in opposition to its ANE context. Through this comparative lens, the Binding of Isaac emerges not merely as a story of obedience, but as a transformative moment in the history of ancient religion—marking a decisive shift toward a moral and monotheistic understanding of divine-human relationships.